The Idea and Creative Imagination in Mind Maps Designs: ثامر حميد رزوقي (Al-Academy, 2020)
The mind map represents a system to solve problems including design problems, because it depends on employing the complex and purposeful mental activity, which starts from a desire based on the search and investigation in order to reach integrated results of scientific thinking, utilizing the objective view of the scientific and practical aspects from various angles. This visual system can develop thinking and shorten the retrieval time of the previous information in order to employ it in the solution finding system, that it evokes past experiences and relates them to current situations, then enables the user to choose a suitable solution for the problems. This visual, educational and circulatory means, at the same time, has specific systems and rules according to the nature of the idea intended to be presented in ways based on excitement and suspense resulting from the creative side in formulating the ideas. Hence, this research is intended to address the idea and the creative imagination in the design of the mental map, and consequently, there are other technical and intellectual aspects include in this respect. The researcher found that the idea and the creative thinking are the first founder for the map project and hence the researcher derived his research idea for these two terms besides designing the mental map.